Descripción de análisis de control de calidad en empaques flexibles producidas en la empresa Resinplast S.A. - Inuma Davila, Lary Frans (2022)
This professional experience report carried out at RESINPLAST S.A., one of the leading companies in Peru in the production of flexible food packaging, describes the quality control analysis in each of the processes to ensure the productivity of flexible packaging. To ensure quality control of flexible packaging that will be used as food packaging, it is necessary to have knowledge of the characteristics of the raw materials used and all the processes involved in their manufacture. As a step prior to the development and manufacture of flexible packaging, it is of utmost importance to know the final application of packaging, which food products are going to be packaged in it, this will involve deciding which raw materials to use and which process parameters to assign to the manufacture of flexible packaging. The above serves as input information for applying appropriate quality control, taking into account the nature and final application of flexible packaging. In the area of Quality Control in which I have been working since May 2016 first as Quality Assurance Analyst and from December 2019 as Head of Quality Assurance Laboratory. Our dedication and delivery to ensure the Quality Control from the input of the raw material, its conversion in each part of the process applying appropriate methods to the samples provided by the production area, in addition to interpreting the information obtained from the parameters throughout the process, this leads us to properly qualify the material produced for its subsequent processes and apply the necessary response actions to deviations in the quality of the product.